Analisis Profitabilitas, Struktur Aset, Dan Pertumbuhan Aset Terhadap Struktur Modal Yang Dimoderasi Likuiditas - Ade Ningrum Mulyasari; Subowo Subowo (Gorontalo Accounting Journal, 2020)
This study aims to analyze the effect of profitability, asset structure, and asset growth on capital structure with liquidity as moderation. The study population is non-financial companies in the LQ45 index listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The sampling technique is purposive sampling. The study sample are 27 companies for 3 years resulting in 81 units of analysis. The data analysis method used is descriptive statistical analysis and inferential statistical analysis using moderation regression analysis (MRA). The results showed that profitability and asset growth were positive and significant for the capital structure, the asset structure had a significant negative effect on the capital structure. Liquidity also moderates the negative influence of profitability on the capital structure. Liquidity is not able to moderate the influence of asset structure and asset growth on capital structure.